Karakteristik Habitat dan Keberadaan Larva Aedes spp. pada Wilayah Kasus Demam Berdarah Dengue Tertinggi dan Terendah di Kota Tasikmalaya - Muhammad Umar Riandi; Upik Kesumawati Hadi; Susi Soviana (ASPIRATOR - Journal of Vector-borne Disease Studies, 2017)
Dengue hemorrhagic fever is a vector-borne disease caused by dengue virus and transmitted by Aedes spp. controlling the mosquito population is currently the only means to prevent dengue outbreaks. The highest dengue case in Tasikmalaya City until July 2015 was in Cikalang village dan the lowest in Cibunigeulis village. This research was an observational study with a cross-sectional design with the aim to determine vector density and Aedes sp. presence risk factor based on habitat characteristic in the highest and lowest dengue cases regions. Aedes spp. breeding sites and their characteristic were examined indoor and outdoor at 100 house each in Cikalang dan Cibunigeulis village. The result showed that in Cikalang, larval presence was mostly found in a non-water-reservoir containers (18.4%), indoor (6.5%), made of cement/soil/rubber (11.1%), open lid (7.5%), <1 litre volume (14.6%), without draining (22.2%), without larvivorous fish (6.5%), with temephos poured (20.3%), and water company household water source (7,7%). As in Cibunigeulis larval habitats was mostly found in a non-water-reservoir containers (8.7%), indoor (0.9%), made of plastic/ceramic/metal/glass (0.9%), open lid (1.1%), <1 litre volume (4%), without draining (2.2%), without larvivorous fish (0.9%), without temephos poured (0.9%), and non-water company household water source (0.9%). Binary logistic regression analysis showed that household water source (p=0,021, OR=13,78) and drainage (p=0,001, OR=0,101) as a risk factor in Aedes larvae inhabit at Cikalang village and none for Cibunigeulis village. These results showed the importance effect of containers draining factor to the presence of Aedes spp. larvae in the highest dengue cases region.